DEVELOPMENT OF HOTS-BASED E-WORKSHEET TO IMPROVE CRITICAL THINKING AND PROBLEM SOLVING ABILITY OF FIFTH GRADE OF PRIMARY SCHOOL STUDENTS - Nursiamti, Harlina; Nurhayati, Kulsum; Aisyah, Siti (UIN Sunan Kalijaga Yogyakarta, 2022)
This research aims to produce a feasible and practical HOTS-based E-Worksheet (LKPD) and to determine its effectiveness in improving the critical thinking and problem solving skills of fifth grade primary school students. This research refers to development stages by Dick & Carey, namely (1) identifying learning objectives, (2) conducting learning analysis, (3) identifying student characteristics, (4) formulating specific objectives, (5) developing test items, (6) developing learning strategies , (7) developing and selecting instructional materials, (8) designing and implementing formative evaluations, and (9) revising learning. The individual experiment in this research involved three students and a teacher, while the small group experiment involved nine students and a teacher. The field experiment covered control and experimental classes. Data were collected through product feasibility scales, teacher and student response scales, observations, pretest questions, posttests, and interviews. The results of the research show that HOTS-based e-worksheet is feasible, practical and effective for improving students’ critical thinking and problem solving skills.